Law Enforcement Perspectives on Children in Conflict with the Law Due to Digital Crimes - Arif Awaludin; Sumiyati Beddu; Semuel Haning; Nining Latianingsih; Irman Syahriar (JURNAL AKTA, 2026)
The rapid growth of digital technology has increased children’s involvement in cyber-related activities, which has consequently raised the number of minors in conflict with the law due to digital crimes. In Indonesia, this phenomenon is intensified by high internet penetration and limited digital literacy among adolescents. This study aims to analyze law enforcement perspectives on children involved in digital crimes within the framework of the juvenile criminal justice system and to identify factors influencing legal responses. This research employs a qualitative approach using a literature study design. Data were collected from academic journals, books, legal regulations, and official institutional reports through systematic searches of Google Scholar, Scopus, and national journal databases. The collected materials were analyzed using content and thematic analysis. The findings indicate that law enforcement perspectives are shaped by legal frameworks, institutional culture, technological complexity, harm severity, and social pressure. Although the Juvenile Criminal Justice System Law emphasizes restorative justice and diversion, its implementation in cybercrime cases remains inconsistent due to the deterrence-oriented provisions of the Electronic Information and Transactions Law. The study concludes that stronger legal harmonization, interdisciplinary training, and public awareness are essential to ensure a more consistent, child-centered justice system in the digital era.